Keanekaragaman Spesies Burung Pada Beberapa Tipe Habitat di Kawasan Pesisir Gerupuk Lombok Tengah - Shihab, Mawaddah; Suana, I Wayan; Hadiprayitno, Gito (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Birds are one of the biodiversity that can be found in the Lombok Coastal Area, including in the Gerupuk Coastal Area. The Gerupuk Coastal Area is one of the tourist destinations in Central Lombok which is currently part of the Mandalika Special Economic Zone. This research aims to determine the diversity of bird species and reveal it in several types of habitat in the Gerupuk Coastal Area, namely mangrove habitat, plantations and settlements.This research is an exploratory descriptive research with an exploratory method. Determining the bird species found during the research refers to the book Birds in the Wallacea Region, the book Birds of Lombok and Sumbawa, and the Burungnesia 3.0 application. Species data and descriptions of birds were analyzed using the Shannon-Wiener Diversity Index formula, Sorensen Similarity Index and Percentage Relative Abundance formula. The results of this research, namely (1) the number of bird species found at the research location was 45 species belonging to 25 families; (2) Passer montanus is a bird species with the highest relative transmitter percentage, namely 10.99%; (3)the species diversity index in each mangrove, plantation and residential habitat is 2.8, 2.9 and 2.3 respectively; (4)the similarity index of residential habitats with plantation habitats is higher (0.54) compared to mangrove habitats (0.41); (5)protected bird species such as Haliastur indus and Falco moluccensis are found on the Gerupuk Coast.